Effects of Denture Cleansers on the Flexural Strength of PMMA Denture Base Resin Modified with ZrO2 Nanoparticles. Issue 3 (26th August 2020) - Gad, Mohammed M.; Abualsaud, Reem; Fouda, Shaimaa M.; Rahoma, Ahmed; Al‐Thobity, Ahmad M.; Khan, Soban Q.; Akhtar, Sultan; Al‐Harbi, Fahad A.
Abstract: Purpose: The additions of zirconium oxide nanoparticles (nano‐ZrO2 ) to denture base materials have produced nanocomposites with satisfactory properties, although there is a lack of research investigating the effects of denture cleansers on these materials. This study aimed to evaluate the effect of denture cleansers on the flexural strength of denture base materials modified with nano‐ZrO2 . Materials and Methods: A total of 270 specimens were fabricated from pure and nano‐ZrO2 reinforced acrylic resins at 2.5% and 5%, resulting in 3 main groups. The groups were further divided into subgroups (n = 10) according to immersion solution (distilled water, Corega, sodium hypochlorite, and Renew) and immersion duration. Flexural strength was measured at baseline (T0 ) in distilled water and after 180 and 365 days of immersion (T1 and T2 ) in denture cleansers. Data were collected and analyzed using repeated measure ANOVA and Bonferroni post hoc tests (α = 0.05). Results: The flexural strength of the nano‐ZrO2 modified denture base material decreased significantly after immersion in different denture cleansers at different immersion durations in comparison to baseline (T0 ) ( p < 0.001). Sodium hypochlorite showed the highest reduction in flexural strength followed by Corega, while Renew cleansing solution resulted in the least change. Conclusion: Denture cleansers can significantly affect the flexural strength of nano‐ZrO2 modified denture base materials and thus should be used cautiously.